Toward an Understanding of Purchase Decision at Totu Thrift House: A Mediation Analysis of Trust - Zikrullah, Aulia (APPS Publications, 2023)
Objective – This study aims to analyze the effect of store atmosphere, variety of products, and social media marketing on purchase decisions with trust as a moderating variable on the consumer Totu Thrift House, Jakarta. Methodology – This research uses a quantitative approach with descriptive and causal research types. Primary data was collected by distributing questionnaires; then, the data was processed using Smart-PLS 3.0. The population of this study is the customers of Totu Thrift House who had visited and followed the store’s Instagram account. Data collection was conducted from March to May 2023, and collected 150 respondents as the samples. Findings – The results showed that the store atmosphere and variety of products positively and significantly affect purchase decisions. Contrary to expectations, the findings revealed that the effect of social media marketing on purchase decisions is insignificant. However, the trust variable is a mediator for all independent variables: store atmosphere, variety of products, and social media marketing, which positively and significantly affect the purchase decision. This research results can be treated as a reference for thrift stores in offering products concerning the store atmosphere and variety of products sold and building trust so that the consumers want to come and are interested in buying in the store. Novelty – Investigating the mediating role of trust in the relationship between the independent variables (Store atmosphere, product variety, and social media marketing) and purchase decisions. This adds depth to understanding the underlying mechanisms influencing consumer behavior in this context.